Análise de adubações e espaçamentos entre linhas nas características biométricas e de produtividade do milho potiguar - Peixoto, Tayd Dayvison Custódio (2014)
The corn crop is important in many contexts of Brazilian agriculture production, as much about economics factors as social factors. Its constitutes one of the main cereals in the world, and, in Brazil, due to changes in management strategies and cultural practices, is achieving high yields. The objectives of this study were to evaluate the biometric characteristicsof production and the productivity of corn variety Potiguar, recommended to the west of the state of Rio Grande do Norte, according to the types of fertilizer and row spacing on irrigated system. This work was conducted at the Experimental Farm Rafael Fernandes, located in the Alagoinha community belonging to the Universidade Federal Rural do Semi-Árido inMossoró-RN, Brazil. The experimental design used was the blocks randomized, in factorial 3 x 2, with four replications, corresponding to three fertilizers (organic, organic-mineral and mineral) and two spacing between rows (80 and 50 cm).The biometric parameters of production: ear length, number of rows of grains per ear and 1000 grains weight were not significantly influenced by factors fertilization and spacing. The mineral fertilization associated with the spacing of 80 cm between rows provided greater results in the production of biometric components diameter ears, weight ears with straw and without straw and grain weight per ear. The factors evaluated, fertilization and spacing, did not affect significantly the grain productivity of corn variety Potiguar